A high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite and its preparation method and application

By introducing NiO and auxiliary components into the ferrite core, a uniform second phase is formed and super-large crystal growth is suppressed, the fracture toughness of the magnetic core is improved, and the problem of limited impact times of the existing ferrite core at high temperature cycle is solved. , realizes high reliability, heat shock resistance, wide temperature and low power consumption ferrite materials.

CN118771876BActive Publication Date: 2025-01-14广东尚朋电磁科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411267163.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-14
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The existing ferrite magnetic core is prone to break when it cycles at a temperature of -40°C to 150°C for more than 1,000 times, resulting in electrical performance failure. The existing low-loss magnetic materials with low-loss resistance to cold and cold shock are limited in this temperature range.

Method used

High reliability, heat shock-resistant wide temperature and low loss ferrite, including Fe2O3, ZnO, NiO and MnO as main components, CaCO3, V2O5, Nb2O5, Co3O4, ZrO2 and Na2SiO3 as auxiliary components, mixed, pre-burned, and ball milling. The mixing, press molding and sintering process is prepared to form a uniform second phase and inhibit the growth of super-large crystals to improve fracture toughness.

Benefits of technology

It can withstand more than 1000 temperature cycle impacts in the temperature range of -40℃ to 150℃, and its power consumption is less than 350mW/cm3 under 100kHz and 200mT, with an initial magnetic permeability of 3100, and has wide temperature and low power consumption characteristics. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite and its preparation method and application, belonging to the technical field of magnetic materials. The present invention introduces a fourth main component NiO on the basis of the main formula of Fe2O3, ZnO and MnO to form a quaternary ferrite, thereby producing a uniform second phase and achieving a self-toughening effect; by introducing CaCO3, V2O5, Nb2O5, Co3O4, ZrO2 and Na2SiO3 as auxiliary components, the toughness of the ferrite is further improved. The high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite provided by the present invention has a power consumption of ≤350mW / cm at 25°C under the conditions of 100kHz and 200mT. 3 , 100℃ power consumption ≤350mW / cm 3 The initial magnetic permeability is 3100. Compared with existing magnetic materials, it has the characteristics of wide temperature and low power consumption, and can withstand temperature cycle shocks from ‑40°C to 150°C for more than 1,000 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic materials, and in particular relates to a high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite and a preparation method and application thereof. Background Art

[0002] In AEC-Q200 reliability testing and actual applications, the reliability problem encountered by transformers and inductors made of ferrite cores is that after 1000 cycles of high and low temperatures from -40°C to 125°C, the cores crack and cause electrical performance failure.

[0003] Ferrite is one of the important functional ceramics. In the early days of ferrite research and production in China, ferrite was once called "magnetic porcelain". Therefore, in terms of mechanical properties, ferrite has the characteristics of ceramic materials. Compared with metal materials, ceramic materials have higher strength and hardness, but their fracture toughness is quite low, 1-2 orders of magnitude lower than that of metal materials. In fact, the fundamental reason why ferrite cores are brittle and broken is often not due to poor strength, but poor fracture toughness. Therefore, improving the fracture toughness of ferrite cores is the fundamental way to solve the problem.

[0004] In recent years, technicians in the industry have done a lot of research to obtain low-power magnetic materials that are resistant to heat shock. For example, patent CN202310772300.0 discloses a low-loss manganese-zinc power ferrite core that is resistant to cold and heat shock and its preparation method. Under the conditions of 100kHz and 200mT, the power consumption of this material at 25℃ is 300-350mW / cm 3 , 100℃ power consumption 300-350mW / cm 3 However, its resistance to temperature cycle shock from -40℃ to 150℃ is 200 times.

[0005] Therefore, there is an urgent need for a magnetic material that can withstand temperature cycling shocks from -40°C to 150°C for more than 1,000 times to solve the above problems. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite and its preparation method and application. The high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite provided by the present invention has the characteristics of wide temperature and low power consumption, and can withstand temperature cycle shocks from -40°C to 150°C for more than 1,000 times.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite, including a main component and auxiliary materials;

[0009] In terms of molar percentage, the main components include Fe2O3 52.58-52.88 mol%, ZnO 9.00-9.25 mol%, NiO 1-3 mol% and the balance MnO;

[0010] The auxiliary materials include CaCO3, V2O5, Nb2O5, Co3O4, ZrO2 and Na2SiO3.

[0011] Preferably, based on the total weight of the main components, the auxiliary materials include CaCO3 0.02-0.04%, V2O5 0.02-0.04%, Nb2O5 0.02-0.03%, Co3O4 0.3-0.4%, ZrO2 0.01-0.04% and Na2SiO3 0.005-0.02%.

[0012] The present invention provides a method for preparing the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite described in the above technical solution, comprising the following steps:

[0013] (1) Fe2O3, ZnO, NiO and MnO are weighed according to mole percentage, and then ball-milled, mixed and pre-calcined to obtain a pre-calcined material;

[0014] (2) Weighing each auxiliary material according to the total weight of the main component, then subjecting the auxiliary material and the pre-sintered material obtained in step (1) to ball milling, pressing and sintering to obtain the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite.

[0015] Preferably, in step (1), the material-water ratio of the ball milling mixture is 1:(1.1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the time is 30-50 min.

[0016] Preferably, in step (1), the pre-calcination temperature is 900-920° C., the feed rate is 2-3 kg / h; and the spinel synthesis degree of the pre-calcined material is 30-40%.

[0017] Preferably, in step (2), the material-water ratio of the ball milling mixture is 1:(1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the time is 70-90 min.

[0018] Preferably, in step (2), zinc stearate is added during the compression molding process; the amount of zinc stearate added is 1-2‰.

[0019] Preferably, in step (2), the sintering includes a heating stage, a heat preservation stage and a cooling stage.

[0020] Preferably, the heating stage is: first heating for 6 hours in an air atmosphere, from room temperature to 1100°C, and then heating from 1100°C to 1305°C in a full nitrogen atmosphere, with a heating rate of 1.5°C / min; the insulation stage is: insulation for 5 hours at 1305°C and an oxygen content of 3.5%; the cooling stage is: cooling from 1305°C to room temperature at a rate of 1.5°C / min.

[0021] The present invention also provides the use of the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite described in the above technical solution in a transformer or inductor.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] The present invention introduces a fourth main component NiO on the basis of the main formula Fe2O3, ZnO and MnO to form a quaternary ferrite, thereby generating a uniform second phase and achieving a self-toughening effect; by introducing CaCO3, V2O5, Nb2O5, Co3O4, ZrO2 and Na2SiO3 as auxiliary components, the ZrO2 undergoes a phase change between a tetragonal structure and a monoclinic structure at about 1150°C, accompanied by a 3-5% volume expansion or contraction; when the ZrO2 particles dispersed in the matrix undergo a phase change, the volume change accompanying the phase change is restricted by the surrounding matrix, thereby hindering the phase change and causing the phase change point temperature to decrease; the degree of phase change temperature decrease is related to the size of the ZrO2 particles; when the size of the ZrO2 particles is less than a certain critical value, the tetragonal ZrO2 phase formed at high temperature can be transformed into a monoclinic ZrO2 phase near room temperature, thereby achieving the purpose of phase change toughening; the auxiliary components Na2SiO3 and V2O5 can effectively inhibit the growth of super-large crystals and achieve the purpose of toughening.

[0024] The high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite provided by the present invention has a power consumption of ≤350mW / cm2 at 25°C under the conditions of 100kHz and 200mT. 3 , 100℃ power consumption ≤350mW / cm 3 The initial magnetic permeability is 3100. Compared with existing magnetic materials, it has the characteristics of wide temperature and low power consumption, and can withstand temperature cycle shocks from -40°C to 150°C for more than 1000 times.

[0025] The preparation method provided by the present invention adopts a conventional sintering temperature, with a maximum sintering temperature of 1305° C., can be sintered together with existing push plate kiln products, does not require separate equipment for sintering, and has low cost. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.

[0028] The embodiment of the present invention provides a high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite, including a main component and auxiliary materials;

[0029] In terms of molar percentage, the main components include Fe2O3 52.58-52.88 mol%, ZnO 9.00-9.25 mol%, NiO 1-3 mol% and the balance MnO;

[0030] The auxiliary materials include CaCO3, V2O5, Nb2O5, Co3O4, ZrO2 and Na2SiO3.

[0031] In a preferred embodiment, the main components include Fe2O3 52.58-52.78 mol%, ZnO 9.00-9.15 mol%, NiO 1-2 mol% and the balance MnO in molar percentage. The present invention forms a quaternary ferrite by introducing a fourth main component NiO on the basis of the main formula of Fe2O3, ZnO and MnO, thereby generating a uniform second phase and achieving a self-toughening effect.

[0032] In a preferred embodiment, based on the total weight of the main components, the auxiliary materials include CaCO3 0.02-0.04%, V2O5 0.02-0.04%, Nb2O5 0.02-0.03%, Co3O4 0.3-0.4%, ZrO2 0.01-0.04% and Na2SiO3 0.005-0.02%. The present invention introduces CaCO3, V2O5, Nb2O5, Co3O4, ZrO2 and Na2SiO3 as auxiliary components, wherein the ZrO2 undergoes a phase change between a tetragonal structure and a monoclinic structure at about 1150°C, accompanied by a 3-5% volume expansion or contraction. When the ZrO2 particles dispersed in the matrix undergo a phase change, the volume change accompanying the phase change is restricted by the surrounding matrix, thereby hindering the phase change and causing the phase change point temperature to decrease. The degree of phase change temperature reduction is related to the size of the ZrO2 particles. When the size of the ZrO2 particles is less than a certain critical value (such as 0.32μm), the tetragonal ZrO2 phase formed at high temperature can be transformed into a monoclinic ZrO2 phase near room temperature, thereby achieving the purpose of phase change toughening. The auxiliary components Na2SiO3 and V2O5 can effectively inhibit the growth of ultra-large crystals.

[0033] The present invention provides a method for preparing the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite described in the above technical solution, comprising the following steps:

[0034] (1) Fe2O3, ZnO, NiO and MnO are weighed according to mole percentage, and then ball-milled, mixed and pre-calcined to obtain a pre-calcined material;

[0035] (2) Weighing each auxiliary material according to the total weight of the main component, then subjecting the auxiliary material and the pre-sintered material obtained in step (1) to ball milling, pressing and sintering to obtain the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite.

[0036] In a preferred embodiment, in step (1), the material-water ratio of the ball milling mixture is 1:(1.1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the grinding time is 30-50 min; the average particle size of the slurry obtained by the ball milling is 1.0-1.1 μm.

[0037] In a preferred embodiment, in step (1), the pre-burning temperature is 900-920°C, and the feed rate is 2-3kg / h. The present invention controls the pre-burning temperature and feed rate within the above range, which is beneficial to ensure the particle size of the subsequent ball milling product. If the pre-burning temperature is too high and the tap density is large, the particle size of the product obtained by ball milling the auxiliary material and the pre-burned material for the same time will be coarse, and because the grinding balls are steel balls, the iron loss of the steel balls is small at this time, and the formula is offset; if the pre-burning temperature is too low, the iron loss increases and the formula is also offset.

[0038] In a preferred embodiment, in step (1), the pre-firing is carried out under air conditions; the pre-firing equipment is a natural gas 500 type rotary kiln; and the rotation speed of the natural gas 500 type rotary kiln is 2N / min.

[0039] In a preferred embodiment, in step (1), the spinel synthesis degree of the pre-sintered material is 30-40%.

[0040] In a preferred embodiment, in step (2), the Na2SiO3 added to the auxiliary material is in the form of Na2SiO3 ethanol solution.

[0041] In a preferred embodiment, in step (2), the material-water ratio of the ball milling mixture is 1:(1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the grinding time is 70-90 min; the average particle size of the slurry obtained by the ball milling mixture is 1.00-1.10 μm.

[0042] In a preferred embodiment, in step (2), the ball milling further comprises mixing the slurry obtained by the ball milling with a PVA solution; the concentration of the PVA solution is 8%, and the amount used is 10% of the slurry mass; the mixing method is stirring, the stirring time is 120 minutes, and the rotation speed is 50 rpm.

[0043] In a preferred embodiment, in step (2), zinc stearate is added during the pressing process; the amount of zinc stearate added is 1-2‰; the density of the standard green body obtained by pressing is controlled at 3g / cm 3 .

[0044] In a preferred embodiment, in step (2), the sintering includes a heating stage, a heat preservation stage and a cooling stage.

[0045] In a preferred embodiment, the heating stage is: first heating for 6 hours in an air atmosphere, from room temperature to 1100°C, and then heating from 1100°C to 1305°C in a full nitrogen atmosphere, with a heating rate of 1.5°C / min; the insulation stage is: insulation for 5 hours at 1305°C and an oxygen content of 3.5%; the cooling stage is: cooling from 1305°C to room temperature at a rate of 1.5°C / min.

[0046] The invention controls the grain size within 5-8 μm by introducing auxiliary components and adopting the above sintering process.

[0047] The present invention also provides the use of the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite described in the above technical solution in a transformer or inductor.

[0048] The room temperature in the embodiments of the present invention refers to "25±2°C".

[0049] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0050] Examples 1-2 and Comparative Example 1

[0051] A method for preparing high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite:

[0052] (1) Fe2O3, ZnO, NiO and MnO were weighed in molar percentage and then ball-milled. The material-water ratio was 1:1.1, the material-ball ratio was 1:5, the grinding balls were ф=3 mm steel balls, and the ball milling time was 30 min to obtain a slurry with an average particle size of 1.0 μm.

[0053] (2) The slurry obtained in step (1) is pre-fired in air using a natural gas 500 type rotary kiln to obtain a pre-fired material with a spinel synthesis degree of 35%; wherein the rotation speed of the natural gas 500 type rotary kiln is 2N / min, the pre-fired temperature is 900°C, and the feed rate is 2kg / h.

[0054] (3) CaCO3, V2O5, Nb2O5, Co3O4 and ZrO2 were weighed according to the total weight of the main components, and then the above auxiliary materials and the pre-sintered material obtained in step (1) were ball-milled and mixed. The material-water ratio of the ball milling was 1:1, the material-ball ratio was 1:5, the grinding balls were steel balls with a diameter of ф=3 mm, and the ball milling time was 70 min to obtain a slurry with an average particle size of 1.00 μm. Then, 10% of the mass of the slurry was added with a PVA solution (concentration of 8%) and a Na2SiO3 ethanol solution. The mixture was stirred at a speed of 50 rpm for 120 min, and zinc stearate was added in an amount of 2‰. The mixture was then pressed and formed to obtain a slurry with a density of 3 g / cm 3 of the green body.

[0055] (4) Sintering the green body obtained in step (3), heating stage: first heating the temperature for 6 hours in an air atmosphere from room temperature to 1100°C, then heating the temperature from 1100°C to 1305°C in a nitrogen atmosphere at a heating rate of 1.5°C / min; holding stage: holding the temperature at 1305°C and an oxygen content of 3.5% for 5 hours; cooling stage: cooling the temperature from 1305°C to room temperature at a rate of 1.5°C / min, to obtain a high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite with a grain size of 5-8 μm.

[0056] The ingredients of Examples 1-2 and Comparative Example 1 are shown in Table 1.

[0057] The ferrites prepared in Examples 1-2 and Comparative Example 1 were kept warm at -40°C for 30 min in a three-chamber high and low temperature test chamber, then switched to 150°C for 30 min, the switching time was 5 min, and then switched to -40°C for 30 min. After 1000 cycles, the performance was tested. The results are shown in Table 1.

[0058] Table 1 Composition and performance of Examples 1-2 and Comparative Example 1

[0059]

[0060] It can be seen from Table 1 that the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite prepared in Example 1-2 has excellent heat-shock resistance.

[0061] Comparative Example 2

[0062] The difference from Example 1 is that ZrO2 is omitted, and the remaining steps are the same as Example 1.

[0063] Comparative Example 3

[0064] The difference from Example 1 is that Na2SiO3 is replaced by SiO2, and the remaining steps are the same as Example 1.

[0065] Comparative Example 4

[0066] The difference from Example 1 is that in step (4), the heating stage: first, the temperature is raised for 6 hours in an air atmosphere, from room temperature to 1100°C, and then in a full nitrogen atmosphere, from 1100°C to 1350°C, with a heating rate of 1.5°C / min; the heat preservation stage: the temperature is kept at 1350°C and the oxygen content is 3.5% for 5 hours; the cooling stage: the temperature is cooled from 1350°C to room temperature at a rate of 1.5°C / min, and the remaining steps are the same as in Example 1.

[0067] The ferrite prepared in Comparative Example 2-4 was kept at -40°C for 30 minutes in a three-chamber high and low temperature test chamber, switched to 150°C for 30 minutes, the switching time was 5 minutes, and then switched to -40°C for 30 minutes. After 1000 cycles, the performance was tested. The results are shown in Table 2.

[0068] Table 2 Properties of ferrites prepared in Comparative Examples 2-4

[0069]

[0070] It can be seen from Table 2 that omitting ZrO2, replacing Na2SiO3 and increasing the sintering temperature will all reduce the thermal shock resistance of ferrite.

[0071] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A high reliability, heat shock resistant, wide temperature and low loss ferrite, characterized in that: Including main ingredients and auxiliary materials; In terms of molar percentage, the main components include Fe2O3 52.58-52.88mol%, ZnO 9.00-9.25mol%, NiO1-3mol% and the balance MnO; Based on the total weight of the main components, the auxiliary materials are CaCO3 0.02-0.04%, V2O5 0.02-0.04%, Nb2O5 0.02-0.03%, Co3O4 0.3-0.4%, ZrO2 0.01-0.04% and Na2SiO3 0.005-0.02%; The method for preparing the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite comprises the following steps: (1) Fe2O3, ZnO, NiO and MnO are weighed according to molar percentage, and then ball-milled and pre-fired to obtain a pre-fired material; the pre-fired temperature is 900-920°C, and the feed rate is 2-3kg / h; (2) Weighing each auxiliary material according to the total weight of the main components, then ball-milling the auxiliary material and the pre-sintered material obtained in step (1), pressing and sintering to obtain the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite; the sintering includes a heating stage, a heat preservation stage and a cooling stage, the heating stage is: first heating for 6 hours in an air atmosphere, from room temperature to 1100°C, then heating from 1100°C to 1305°C in a full nitrogen atmosphere, with a heating rate of 1.5°C / min; the heat preservation stage is: heating for 5 hours at 1305°C and an oxygen content of 3.5%; the cooling stage is: cooling from 1305°C to room temperature at a rate of 1.5°C / min.

2. The method for preparing the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite according to claim 1, characterized in that: The following steps are involved: (1) Fe2O3, ZnO, NiO and MnO are weighed according to molar percentage, and then ball-milled and pre-fired to obtain a pre-fired material; the pre-fired temperature is 900-920°C, and the feed rate is 2-3kg / h; (2) Weighing each auxiliary material according to the total weight of the main components, then ball-milling the auxiliary material and the pre-sintered material obtained in step (1), pressing and sintering to obtain the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite; the sintering includes a heating stage, a heat preservation stage and a cooling stage, the heating stage is: first heating for 6 hours in an air atmosphere, from room temperature to 1100°C, then heating from 1100°C to 1305°C in a full nitrogen atmosphere, with a heating rate of 1.5°C / min; the heat preservation stage is: heating for 5 hours at 1305°C and an oxygen content of 3.5%; the cooling stage is: cooling from 1305°C to room temperature at a rate of 1.5°C / min.

3. The preparation method according to claim 2, characterized in that: In step (1), the material-water ratio of the ball milling mixture is 1:(1.1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the time is 30-50 min.

4. The preparation method according to claim 2, characterized in that: In step (2), the material-water ratio of the ball milling mixture is 1:(1-1.2), the material-ball ratio is 1:(5-6), the grinding balls are steel balls with a diameter of ф=3 mm, and the time is 70-90 min.

5. The preparation method according to claim 2, characterized in that: In step (2), zinc stearate is added during the compression molding process; the amount of zinc stearate added is 1-2‰.

6. Application of the high-reliability, heat-shock-resistant, wide-temperature, low-loss ferrite according to claim 1 in transformers or inductors.

Citation Information

Patent Citations

  • Cold and hot shock resistant low-loss manganese-zinc power ferrite magnetic core and preparation method thereof

    CN116693282A

  • NiMnZn ferrite material and preparation method thereof

    CN102054552A

  • High-frequency low-loss FeMnZnNi ferrite material and preparation method thereof

    CN111362680A

  • Wide-temperature-range ultralow-power-consumption manganese-zinc ferrite material and preparation method thereof

    CN112707723A

  • Additive for preparing permanent magnetic ferrite pre-sintering material and application of additive

    CN118515475A